The Impact of the Law No 4/2023 on the Development and Strength of the Financial Sector (P2SK): Is Crypto Getting Brighter? - Eri Puspita, Rosana; Iskandar, Iskandar; Tandio, Tjondroargo (Otoritas Jasa Keuangan, 2024)
This study aims to analyze crypto market conditions so they can formulate policy recommendations for OJK. Crypto market conditions were observed using a netnographic approach, using a total sample of 6,267 netizen comments. Data was extracted with NAWALA software, processed with NVIVO, and policy selected with MULTIPOL. The results show a better dynamic in the crypto market development in Indonesia after the issuance of the Law, even though many dynamics still occur. This study suggests that the Financial Services Authority (OJK) take different policies in 2024, 2025, and 2026 in supporting the development of crypto assets.